Hepatic toxicity by methotrexate with weekly single doses associated with folic acid in rheumatoid and psoriatic arthritis. What is its real frequency? - García, Daniel S.; Saturansky, Etel I.; Poncino, Daniel; Martínez-Artola, Yamila; Rosenberg, Silvia; Abritta, Gloria; Ascimani-Peña, Carlos; Cravero, Amerys (Annals of hepatology, 2019)
Liver injury caused by methotrexate (MTX) has mostly been investigated without applying criteria for the assessment of causality of drug induced liver injury (DILI). Hence, the existence of DILI by MTX in many cases is debatable. This study aimed to describe the frequency and characteristics of liver injury caused by MTX, applying DILI diagnostic criteria. Rheumatoid arthritis (RA) and psoriatic arthritis (PsA) patients who were treated with MTX in association with folic acid were included. Serial determinations of alanine amino transferase (ALT) and aspartate amino transferase (AST) were performed. The Roussel Uclaf Causality Assessment Method (RUCAM) was applied in cases of increases of ALT/AST over 1.5 upper limit of normal. Liver biopsy was considered when the total cumulative dosage (TCD) of MTX was ≥3.5g. A total of 43 patients were analyzed (median follow up 32 (range: 1–48) months; 3.33 ALT/AST determinations per year). Five subjects presented an increase of ALT/AST. All presented a RUCAM score for MTX≤2 (improbable). Three had a RUCAM score for non-steroidal anti-inflammatory drugs ≥7 (probable) and two patients presented non-alcoholic fatty liver disease. Five patients with no other cause for liver disease consented to liver biopsy (TCD MTX: median 5.1; range: 3.5–7.4g). No significant fibrosis or steatosis was evident on histology. No biochemical or significant histological liver toxicity for MTX was demonstrated when applying causality criteria for DILI. More studies with this methodology are necessary in order to improve the assessment of its frequency.